Automated Raman based cell sorting with 3D microfluidics. Issue 22 (15th October 2020) - Lyu, Yingkai; Yuan, Xiaofei; Glidle, Andrew; Fu, Yuchen; Furusho, Hitoshi; Yang, Tianxin; Yin, Huabing
Abstract : We report an automated, high throughput Raman activated cell sorter using three-dimensional microfluidics (3D-RACS). Abstract : Raman activated cell sorting has emerged as a label-free technology that can link phenotypic function with genotypic properties of cells. However, its broad implementation is limited by challenges associated with throughput and the complexity of biological systems. Here, we describe a three-dimensional hydrodynamic focusing microfluidic system for a fully automated, continuous Raman activated cell sorting (3D-RACS). The system consists of a 3D printed detection chamber (1 mm 3 ) that is integrated with a PDMS based sorting unit, optical sensors and an in-line collection module. It has the ability to precisely position cells in the detection chamber for Raman measurements, effectively eliminating spectroscopic interference from the device materials. This enables the sorting of a range of cell sizes (from 1 μm bacteria to 10's μm mammalian cells) with stable operation over >8 hours and high throughput. As a proof-of-concept demonstration, Raman-activated sorting of mixtures of Chlorella vulgaris and E. coli has demonstrated a purity level of 92.0% at a throughput of 310 cells per min. The platform employed in this demonstration features a simple "Raman window" detection system, enabling it to be built on a standard, inverted microscope. Together with its facile and robust operation, it provides a versatile tool for function-based flow cytometry and sorting applications in the fields of microbiology, biotechnology, life science and diagnostics.